Actividades desarrolladas en establecimiento farmacéutico privado Inkafarma Paijan agosto 2015 –julio 2016” - Vásquez Villacampa, Kenyo Pascual (2016)
In this report pre practices professional development activities in the pharmaceutical development of the chain of drugstores located in Inkafarma P.J. Alto Paijan Mz 37 Lote 2C La Libertad department during the period august 2015 to july 2016 is presented. The internship in this company was made under the guidance of DT. Maribel Tapia Idrogo, pharmaceutical chemist in charge of that establishment. The report describes the various activities during the stay in the company as Assistant Pharmacist, which is considered as a boss in turn described. Being in charge and pharmacy technicians, cashiers and storekeepers. The function performed during that period was basically in maintaining efficient management in this establishment, both in care and quality patient guidance as issued in controlling and stored in local medicines